Assessing the antiproliferative effect of biogenic silver chloride nanoparticles on glioblastoma cell lines by quantitative image‐based analysis - Nathalia Müller; Mateus Eugenio; Luciana F. Romão; Jorge Marcondes de Souza; Soniza V. Alves‐Leon; Loraine Campanati; Celso Sant’Anna (IET Nanobiotechnology)
Abstract Glioblastoma is the most life‐threatening tumour of the central nervous system. Temozolomide (TMZ) is the first‐choice oral drug for the treatment of glioblastoma, although it shows low efficacy. Silver nanoparticles (AgNPs) have been shown to exhibit biocidal activity in a variety of microorganisms, including some pathogenic microorganisms. Herein, the antiproliferative effect of AgCl‐NPs on glioblastoma cell lines (GBM02 and GBM11) and on astrocytes was evaluated through automated quantitative image‐based analysis (HCA) of the cells. The cells were treated with 0.1‐5.0 μg/ml AgCl‐NPs or with 9.7‐48.5 μg/ml TMZ. Cells that received combined treatment were also analysed. At a maximum tested concentration of AgCl‐NPs, GBM02 and GBM11, the growth decreased by 93% and 40%, respectively, following 72 h of treatment. TMZ treatment decreased the proliferation of GBM02 and GBM11 cells by 58% and 34%, respectively. Combinations of AgCl‐NPs and TMZ showed intermediate antiproliferative effects; the lowest concentrations caused an inhibition similar to that obtained with TMZ, and the highest concentrations caused inhibition similar to that obtained with AgCl‐NPs alone. No significant changes in astrocyte proliferation were observed. The authors’ findings showed that HCA is a fast and reliable approach that can be used to evaluate the antiproliferative effect of the nanoparticles at the single‐cell level and that AgCl‐NPs are promising agents for glioblastoma treatment.